MENINGKATKAN KEMAMPUAN BAHASA INGGRIS SISWA SD GMIT TUATUKA DENGAN MEDIA KARTU HURUF - Viktorius P. Feka; Yohanis Taniu; Agnes M.D. Rafael; Selfiana T. M. Ndapa Lawa; Darius Y. Nama; Christmas P. Ate; Kristina N. Nahak; Yonly A. Benufinit (FKIP Universitas Citra Bangsa, 2023)
This community service aims to enable students to recognize and pronounce English alphabets accurately through alphabet flashcards. In addition, this kind of activity is conducted to encourage students to form words and create simple sentences. This activity employs methods of lecture, discussion, and demonstration. The results of this activity show that students are now able to pronounce the English alphabet and construct words and simple sentences. Consequently, students have become interested in learning English.